The impact of Bedouin agricultural gardens on biodiversity in South Sinai, Egypt - Norfolk, Olivia (2015)
This project assesses the impact of traditional Bedouin agricultural gardens on biodiversity within the St Katherine Protectorate, South Sinai, Egypt. The Bedouin harvest rainwater from intermittent flash floods, allowing them to cultivate a wide range of trees and crops throughout the year. Rainwater harvesting techniques such as these can improve crop yields and enhance food security in arid regions, but this is one of the first studies to address the impact upon dependent wildlife. The results showed that the irrigated gardens support a more diverse plant community than the surrounding unmanaged habitat, providing an abundance of floral resources which in-turn enhance pollinator abundance and species richness. The inclusion of a diversity of culturally important minority crops had a dramatic effect upon the structure of plant-pollinator visitation networks, with cultivated plants supplementing the resources provided by wild flowers. The presence of simultaneously flowering crops also had a positive effect upon pollination services to the primary crop (almond), by attracting higher densities of wild pollinators into the gardens and facilitating enhanced fruit set. The higher abundance of resources within the gardens also had a positive impact upon birds in the region, with gardens supporting higher densities and species richness than the unmanaged habitat. Gardens were particularly important for migratory species, providing an important stop-over for numerous small passerines. In conclusion this study provides evidence that irrigated agriculture in arid environments has the potential to increase biodiversity above that found in the un-managed environment. The implications on a local scale are that traditional Bedouin practices can have a positive influence on wildlife within the Protectorate, thus initiatives to fund and support gardeners should be encouraged. On a wider scale the results suggest that rainwater harvesting may provide a sustainable mechanism for increasing food security in arid regions, offering a low-cost strategy for increasing agricultural productivity that does not undermine the biodiversity on which it depends.